Pengaruh Affilliate Marketing, Live Streaming, Online Customer Review Dan Online Customer Rating Terhadap Minat Beli Dan Keputusan Pembelian Online Dalam Tiktokshop : Survei Konsumen Produk Skintific Pengguna Tiktok Shop - Nur Afifa Agustin; Amma Fazizah (Pusat Riset dan Inovasi Nasional, 2023)
This research purpose to determine the influence of Affiliate Marketing, Live Streaming, Online Customer Reviews and Online Customer Rating on Purchase Intention and Purchase Decisions. This research uses an explanatory research approach with quantitative methods. Research data was obtained by distributing paperless questionnaires using Google Form to 114 respondents. The data analysis technique uses path analysis in the SPSS 16 application. The research results are as follows: (1) Affiliate marketing (X1) has a positive and significant effect on Purchase Intention (Y1). (2) Live Streaming (X2) has a positive and significant effect on Purchase Intention (Y1). (3) Online Customer Reviews (X3) have a positive and significant effect on Purchase Intention (Y1). (4) Online Customer Rating (X4) has a positive and significant effect on Purchase Intention (Y1). (5) Affiliate marketing (X1) has a positive and significant effect on Purchasing Decisions (Y2). (6) Live Streaming (X2) has a positive but not significant effect on Purchase Decision (Y2). (7) Online Customer Reviews (X3) has a positive but not significant effect on Purchase Decision (Y2). (8) Online Customer Rating (X4) has a positive but not significant effect on Purchase Decision (Y2). (9) Purchase Intention (Y1) has a positive and significant effect on Purchase Decision (Y2).